Ekonomické a správní nástroje ochrany krajinného rázu - Guth, Jiří; Johanisová, Naděžda; Filipová, Martina (Masarykova univerzita, Fakulta sociálních studií, Katedra environmentálních studií, 2010)
The publication analyses and discusses legal and financial tools, including international strategies and policies, relevant to the protection of landscape character with a focus on agricultural impact in the Czech Republic. The first section summarises the available Czech literature on the subject and includes an analysis of the changes in scale of Czech farms after 1989. The second section summarises relevant financial instruments and their influence on landscape character. In the third section, a more detailed analysis of selected tools is attempted, including several case studies describing.